A review of Clostridioides [Clostridium] difficile occurrence through the food chain. (February 2019) - Candel-Pérez, Carmen; Ros-Berruezo, Gaspar; Martínez-Graciá, Carmen
Abstract: The epidemiology and transmission of Clostridioides difficile, particularly for community-associated infections, are not completely understood. Although there have been no confirmed cases of any foodborne disease caused by C. difficile, its occurrence in livestock and foods suggests that contaminated food products with spores could be a vehicle to spread C. difficile infection. This review proposes potential sources of C. difficile infection in the community and contamination routes of food products. Based on European research, it also summarizes the occurrence and organism characterization of C. difficile in animals at slaughterhouses and in human foods. Most of the analyzed literature reported prevalence in retail foods of less than 8%, including microorganism belonging to the ribotype 078, an important hypervirulent strain involved in disease in humans. This prevalence in Europe is underestimated, being lower that reported in North America (rates up to 42%), probably due of the lack of an ISO procedure for the detection of C. difficile in food products that preclude the comparison of prevalence data from different studies. The survival and growth of vegetative C. difficile cells and the resistance of its spores in foods are discussed as well as the risk factors of acquisition CDI from food products. Highlights: Potential sources of community-associated C. difficile infection. Food products as a vehicle to spread community-associated C. difficile infection. Routes of contamination of food products by C. difficile. Isolation rates of C. difficile at slaughterhouses and in retail foods. Exposure assessment of C. difficile in food products.